Pla a 2 and Pla a 3 reactivities identify plane tree‐allergic patients with respiratory symptoms or food allergy. Issue 4 (19th January 2017) - Scala, E.; Cecchi, L.; Abeni, D.; Guerra, E. C.; Pirrotta, L.; Locanto, M.; Giani, M.; Asero, R.
Abstract: Nine hundred and thirty‐nine rPla a 1, nPla a 2, and rPla a 3 ImmunoCAP ISAC reactors were studied. nPla a 2 pos MUXF3 pos but Pla a 1/2 neg subjects were excluded from the study because they were cross‐reactive carbohydrate determinant reactors. Among the 764 remaining participants, 71.9% were Pla a 3 pos, 54.1% Pla a 2 pos, and 10.9% Pla a 1 pos . Among Pla a 3 reactors, 89.6% were Pru p 3 pos and 86.8% Jug 3 pos, but the strongest IgE recognition relationship was observed between Pla a 3 and Jug r 3. Distinctive clinical subsets could be documented among plane tree‐allergic patients. Pla a 3 reactors had both local and systemic food‐induced reactions, but lower past respiratory symptoms occurrence. Pla a 2 reactivity was associated with respiratory symptoms but inversely related to systemic reactions to food. Cosensitization to Pla a 2 and Pla a 3 was associated with a lower past incidence of severe food‐induced reactions.